Long-term Results After Hyaluronan-based MACT for the Treatment of Cartilage Lesions of the Patellofemoral Joint. (March 2016) - Kon, Elizaveta; Filardo, Giuseppe; Gobbi, Alberto; Berruto, Massimo; Andriolo, Luca; Ferrua, Paolo; Crespiatico, Ilaria; Marcacci, Maurilio
Background: Cartilage lesions of the patellofemoral joint are a challenging condition. Hyaluronan-based matrix-assisted autologous chondrocyte transplantation (MACT) has been shown to offer a significant improvement in the short term but has a tendency to worsen at midterm follow-up. Hypothesis: Patients treated with MACT for lesions of the articular surface of the patellofemoral joint will present further clinical worsening at long-term follow-up. Study Design: Case series; Level of evidence, 4. Methods: Thirty-two patients with full-thickness chondral lesions in the patellofemoral joint were treated with hyaluronan-based MACT and were prospectively evaluated preoperatively and at 2-, 5-, and 10-year follow-up. The mean defect size was 4.45 cm 2 . There were 20 lesions located on the patella and 8 on the trochlea, and 4 patients had multiple lesions: 3 with patellar and trochlear lesions and 1 with patellar and lateral femoral condyle lesions. Results were evaluated using International Knee Documentation Committee (IKDC) subjective scores, EuroQol visual analog scale (EQ VAS) scores, and Tegner scores. Surgical and clinical failures were documented. Results: All scores showed a statistically significant improvement at 2-, 5-, and 10-year follow-up with respect to the preoperative level. No worsening was observed at the last follow-up, and results were stable up to 10 years. The improvement in mean (±SD) outcome scores from preoperatively to 2-, 5-, and 10-year follow-up was as follows: IKDC, from 46.0 ± 19.8 to 77.1 ± 17.4, 72.0 ± 20.4, and 78.6 ± 16.4, respectively; Tegner, from 2.5 ± 1.4 to 4.7 ± 1.8, 4.7 ± 1.6, and 4.4 ± 1.5, respectively; and EQ VAS, from 56.9 ± 18.4 to 81.7 ± 13.2, 79.2 ± 17.9, and 78.9 ± 1.7, respectively. Four patients did not achieve significant clinical improvement, and 1 of these patients required further surgical treatment. All failures were female patients with patellar defects, and 3 of them had degenerative lesions and underwent a previous or combined realignment procedure. Conclusion: The clinical results of hyaluronan-based MACT treatment of chondral lesions of the patellofemoral joint do not worsen over time but remain stable and show a low rate of failure at long-term follow-up.